Paul's Principles of Pastoral Care in Acts 20:17-38 and His Challenges to Pastoral Leaders - Budiyono Budiyono; Jani Jani (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2024)
This article aims to analyze the pastoral service practices of Paul that are worthy of being imitated by the local church leaders today by focusing on the content of his farewell speech to the elders of the church in Ephesus based on Luke's record in Acts 20:17-38. The narrative hermeneutic method will analyze each statement related to his service actions. The results of the analysis show the pastoral service practices that are lived, taught, and need to be imitated by church leaders today in Indonesia. The study results show that the Apostle Paul presents the principles of pastoral service that are timeless and relevant to the context of local church service today. The fundamental principles he taught and the challenges pastoral leaders face today are: First, making the most of time. Pastoral leaders in the present era are challenged to maximize every opportunity in their service, especially amid many distractions and demands of the times. Second, he emphasizes the importance of humility in service. Today's leaders must be aware of the danger of arrogance and constantly realize their trustworthy source of strength. Third, Paul not only serves with enthusiasm but also with deep emotion. This challenges today's church leaders to engage emotionally, empathize with the congregation, and feel grief and joy with them. Fourth, he often faces threats and dangers in his service. Church leaders must be ready to face challenges, especially when voicing the truth of the Bible in an increasingly secular cultural context. Fifth, serving with teaching. He emphasizes the importance of correct and profound teaching. In the information age full of false teachings, pastoral leaders are challenged to continue to provide teaching based on the Bible and relevant to their congregation.